2006
DOI: 10.1103/physrevb.73.224408
|View full text |Cite
|
Sign up to set email alerts
|

Absence of ferromagnetism in bulk polycrystallineZn0.9Co0.1O

Abstract: The atomic structure and the magnetic properties of 5 and 10 at. % Co-doped ZnO samples prepared by a high-pressure and high-temperature method have been investigated by various techniques, including x-ray diffraction with Rietveld refinements, scanning electron microscopy, high-resolution transmission electron microscopy, nanometer-sized element mapping, x-ray photoelectron spectroscopy, near-edge x-ray absorption fine structure, and extended x-ray absorption fine structure and magnetization measurements. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 43 publications
3
43
1
Order By: Relevance
“…Paramagnetism is expected to arise from the exchange interaction of magnetic moments mediated by the defects in doped nanoceramics. Similar paramagnetic behavior was reported for transition metal doped ZnO and SnO 2 [29][30][31][32][33]. Adhikari et al [34] observed the absence of ferromagnetic and antiferromagnetic ordering in Gd doped SnO 2 nanoparticles.…”
Section: Resultssupporting
confidence: 71%
“…Paramagnetism is expected to arise from the exchange interaction of magnetic moments mediated by the defects in doped nanoceramics. Similar paramagnetic behavior was reported for transition metal doped ZnO and SnO 2 [29][30][31][32][33]. Adhikari et al [34] observed the absence of ferromagnetic and antiferromagnetic ordering in Gd doped SnO 2 nanoparticles.…”
Section: Resultssupporting
confidence: 71%
“…In one case, giant magnetic moment of 6.1 l B /Co has been reported in the insulating ZnO:Co thin films [6], whereas in some other cases, RTFM is either claimed to be carrier mediated [7,8] or attributed to the presence of Co clusters [13][14][15]. Contrary to the above, ZnO:Co films are reported to be paramagnetic [16][17][18].…”
Section: Introductionmentioning
confidence: 86%
“…The RTFM observed in these oxide semiconductors has opened a new window for potential application of these materials in realization of spintronic devices. However, the experimental findings on the room temperature ferromagnetic ordering in transition metal doped oxide semiconductors reported so far are at large variance and the nature (i.e., extrinsic or intrinsic) and origin of room temperature ferromagnetism is yet far from being clearly understood [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In our earlier study on chemically synthesized nanocrystalline ZnO:Co powder samples [3][4][5], we have established the presence of RTFM in these samples as an intrinsic effect.…”
Section: Introductionmentioning
confidence: 99%
“…12 A wide range of contradictory experimental results, debating the success [13][14][15][16][17][18] versus failure [19][20][21][22][23] of obtaining a T c above room temperature based on such dilute magnetic oxide systems, have injected much excitement about the origin of ferromagnetism in these systems. Among all these systems, ZnO belongs to the list of the most suitable candidates for spintronics application due to its abundance and environment-friendly nature and also due to its potential as a suitable optoelectronic material with a wide band gap ͑ϳ3.3 eV͒ and high exciton binding energy of 60 meV.…”
Section: Introductionmentioning
confidence: 99%